PENGARUH RELIGIUSITAS DAN PENGALAMAN KERJA TERHADAP KUALITAS AUDIT (Studi pada Kantor Akuntan Publik di Kota Banda Aceh) - Nazariah Nazariah; Ismayli Ismayli (Unitri Press, 2021)
The purpose of this study was to see the level of auditors' reliability and work experience that can affected the quality of the audit performed. This study is descriptive, with sample in this study were 37 auditors. In determining the sample used saturated sampling and field research methods. While the analysis tool used is multiple linear regression. From the analysis, it is found that the auditor's religiosity will affect the audit quality as well as the work experience, that the audit quality is not only in terms of high education alone but is also influenced by the auditor's work experience.